Modeling the Institutional Factors Affecting the Utilization of Entrepreneurial Capacities (EC) in Sports Tourism in Iran - Reza Heydari; Ahmad Mahmoudi; Bahador Azizi; Sahar Pirjamadi; Saman Mehri (Research in Sport Management and Marketing)
Purpose: This study aimed to modeling the institutional factors affecting the utilization of entrepreneurial capacities in sports tourism in Iran.Method: The research was applied in terms of purpose and analytical in terms of type, which was conducted as a survey. The statistical population included all entrepreneurs in the field of sports tourism in the country, of which 384 people were randomly selected as a sample, and finally 367 questionnaires could be examined. To collect data, a researcher-made questionnaire taken from the research of Heydari et al. (2021), was used. To confirm the validity of the questionnaire, the opinions of 11 sports management experts were used. Cronbach's alpha test was used to determine the reliability of the tool, and its value was 0.92.Results: Findings revealed that the necessary institutional factors in the legal-administrative, normative-cultural, cognitive-educational, and guiding-supportive dimensions can increase entrepreneurial behavior in this field by increasing the ability and willingness of entrepreneurs to utilization entrepreneurial capacities in sports tourism.Conclusion: Results suggest that to grow the sports tourism industry in developing countries like Iran, many factors with greater convergence should be involved. In this regard, the existence of a suitable legal, normative, supportive and educational environment will affect the ability and willingness of market leaders to identify and utilization the entrepreneurial opportunities of this emerging industry in the country.